Predicting the development of overweight and obesity in children between 2.5 and 8 years of age: The prospective ABIS study - Karel Duchen; Mike Jones; Åshild Olsen Faresjö; Tomas Faresjö; Johnny Ludvigsson (Wiley, 2020)
Summary Background A relationship between overweight and obesity early in life and adolescence has been reported. The aim of this study was to track changes in overweight/obesity in children and to assess risk factors related to the persistence of overweight/obesity between 2.5 and 8 years. Study design Children who participated in all three follow‐ups at 2.5, 5 and 8 years in the prospective cohort All Children in Southeast Sweden (ABIS) (N = 2245, 52.1% boys and 47.9% girls) were classified as underweight, normal, overweight or with obesity, and changes within categories with age were related to risk factors for development of obesity in a multivariate analysis. Results The prevalence of overweight and obesity between 2.5 and 8 years was 11%-12% and 2%-3%, respectively. Children with normal weight remained in the same category over the years, 86% between 2.5 to 5 years and 87% between 5 and 8 years. Overweight and obesity at 5 and 8 years were positively related to each other (p < 0.0001 for both). High level of TV watching at 8 years and high maternal body mass index (BMI) when the child was 5 years were related to lower probability to a normalized ISO‐BMI between 5 and 8 years of age (p < 0.05 for both). Conclusion Children with ISO‐BMI 18.5 to 24.9 remain in that range during the first 8 years of life. Children with overweight early in life gain weight and develop obesity, and children with obesity tend to remain with obesity up to 8 years of age. TV watching and high maternal BMI were related to lower probability to weight normalization between 5 and 8 years of age. A multidisciplinary approach to promote dietary and physical activity changes in the entire family should be used for the treatment and prevention of overweight and obesity in early childhood.